Impact of Watershed Development Programmes of Watershed OrganizationTrust (WOTR) on the Beneficiaries in Ahmednagar District - Khalache, P.G.; Gaikwad, J.H. (Indian Journal of Extension Education, 2011)
WOTR (Watershed Organization Trust) is one of the non government organization working in Maharashtra since 1993. This trust constructed 36 watersheds in Maharashtra. The critical coverage area of the project is 31,536 hectares. it was observed that there was a need to undertake the study by the professional institutional source to examine the impact of the Watershed project on agricultural development and extent of the benefits derived by the beneficiaries from programme implemented by the WOTR. Results revealed that higher proportion of the beneficiaries i.e. 78.00 per cent in the middle age category of 36 to 50 years, while, in case of the non beneficiaries 75.00 per cent belonged to the middle age category. A majority (69.00 per cent) of the beneficiaries was educated while; in case of non-beneficiaries most of them (48.00 per cent) were illiterate. Most of the beneficiaries (62.00 per cent) and non-beneficiaries (68.00 per cent) together possessed Class-III soil type. A majority of the beneficiaries (64.00 per cent) and non-beneficiaries (51.00 per cent) used medium level of sources of information. The social participation of beneficiaries was found to be higher than that of non beneficiaries. Forty two per cent of beneficiaries had land holding up to 1 ha. while, 62.00 per cent of the non-beneficiaries had land holding up to 1 ha. Relatively higher per cent of beneficiaries (85.00) had annual income in between Rs. 21,501 to 1,50,000 than the non-beneficiaries(60.00). Most of the beneficiaries i.e. 60.00 were found to be from medium category of socio-economic status while, 61.00 per cent of the non-beneficiaries were found to be from low category of socio-economic status. It is also observed in the study that the crop production and productivity, cropping intensity, employment, annual income, cropping pattern and socio economic status were found to be changed in positive direction in case of the beneficiary respondents. Over all impact of watershed project was found to be in the medium category for the beneficiary respondents while, it was in low category for the non-beneficiary respondents.